Активизация предпринимательских структур в посткризисном оживлении экономики (Путеводитель предпринимателя, 2020)
This article is dedicated to analysis of current small and medium-sized enterprises’ in Russian Economy with substantiation of entrepreneurship as factor which increases the competitiveness of economy. The article describes main difficulties of entrepreneurial structures in its development and specifies its reasons.